Sports and physical activities in Islam: reflections of Muslim participation - Abd Rahim, Badruel Hairiel; Md Jani, Haizuran; Mohamad Diah, Nurazzura (Jabatan Penerbitan, Bahagian Penyelidikan dan Inovasi (BPI), Kolej Universiti Islam Pahang Sultan Ahmad Shah (KUIPSASP, 2019)
In this article, we examine the understanding of sports and physical activities from the Islamic perspective. We aim at discussing the scholarly views on sports, from both the Muslim as well as Western researchers. We also scrutinise the selected interpretation from the Qur 'an and Hadith as well as debates on barriers in sports and physical activities faced by the practising Muslim. To obtain relevant information for this paper, we have analysed selected articles in strengthening our views. This article is projected to Muslim as we are inevitably participating in sports and physical activities. In a shell, we hoped to contribute to the enrichment of literature in sports and physical activities literature in Islam and used as a guideline for stakeholders in formulating the proper policies for sports and physical activities in the multi-religious and multi-ethnic environments like Malaysia.